Comparing MCDM Methods of AHP, TOPSIS and PROMETHEE: A Study on the Selection of Ship Main Engine System - Sümeyra Uzun; Halim Kazan (Journal of Transportation and Logistics)
Decision is optimum reaction in the face of situations, but encountered problems can be among more than one alternatives in accordance with precise purpose and according to certain criteria. Going for multiple criterion decision making methods fend us to reach optimum solutions in the case of facing decision problems. After informing regarding with studies, multiple criterion decision making methods were talked over (discussed) such as AHP, TOPSIS and PROMETHEE. Discussed methods were implemented to the selection of main engine which is important in the field of vessel building and results were compared. The purpose of implement these methods is to choose the most appropriate machine for the Project. The problem of choosing the most appropriate main engine was talked over on this study for fishing vessel NB25 Wartsila. Totally 12 criteria were ascertained and it was tried to choose the most appropriate main engine among 7 engines according to determined criteria. Decision problem was tried to solve with AHP, TOPSIS and PROMETHEE methods, and the results were compared. At the end of comparison, it was observed that AHP AND PROMETHEE methods gave us close results to each other. The results of AHP and PROMETHEE methods showed consistency in ( with) actual situation.